Extracellular electron transfer capability of oral pathogens Aggregatibacter actinomycetemcomitans and Porphyromonas gingivalis. Issue 7 (8th June 2022) - Naradasu, Divya
Abstract : Polymicrobial oral biofilms, which consist of fermentative-bacteria, are associated with periodontitis, gingivitis and cause systemic diseases 1 . Unlike aerobic-respiration, fermentation does not require electron acceptors like O2; and redox-cycling of biological electron-carriers, like NADH, drives the intracellular oxidation and reduction of organic-substrates 2 . Thus, the energy gain is potentially lower than that of respiratory metabolism; however, the high pathogenic activity in anaerobic conditions remained ambiguous 3 . Afew studies have shown that fermentative gut microbes are capable ofreducing external electron acceptors viaextracellular electron transfer (EET) 4-7 . EET, a phenomenon initially found in environmental-bacteria, where metabolically generated electrons are transferred to external electron-acceptors through an outer-membraneredoxprotein complex 8-9 . Thus, the pathogens colonization in the human microbiome may be supported by their EET capability and is important to explore such potentiality. Here, we electrochemically characterized oral-biofilm pathogens Aggregatibacter actinomycetemcomitans and Porphyromonas gingivalis, to examine their EET ability with lactate/glucose. Both strains showed current production on an electrode surface, associated with consumption of substrate 10 . The addition of antibiotics that suppress the biosynthesis of membrane or protein showed a significant current decrease, demonstrating that current production reflects the cellular-activity. Further, transmission-electron-microscopy of 3, 3‡-diaminobenzidine (DAB) stained cells revealed the presence of redox-enzymes on the cell-membrane suggesting a potential EET mechanism via membrane proteins9. These results could be a basis to reevaluate human oral pathogens from an electroactive point of view. The identified EET activity of the two strains can be utilized for an effective test for assessing the impact of antibacterial compounds on the pathogen cellular-activity on an electrode 11 .